Survival model database of human digestive system cells exposed to electroporation pulses: An in vitro and in silico study - Xuan Han; Xuan Han; Nana Zhang; Nana Zhang; Yuchi Zhang; Yuchi Zhang; Zhuoqun Li; Zhuoqun Li; Yingxue Wang; Yingxue Wang; Lujing Mao; Lujing Mao; et al. (Frontiers Media S.A., 2022)
Background and objectivesThis study aimed to establish a mathematical survival model database containing cell-specific coefficients from human digestive system cells exposed to electroporation pulses (EPs).Materials and methodsA total of 20 types of human digestive system cell lines were selected to investigate the effect of EPs on cell viability. Cell viability was measured after exposure to various pulse settings, and a cell survival model was established using the Peleg-Fermi model. Next, the cell-specific coefficients of each cell line were determined.ResultsCell viability tended to decrease when exposed to stronger electric field strength (EFS), longer pulse duration, and more pulse number, but the decreasing tendency varied among different cell lines. When exposed to a lower EFS (<1,000 V/cm), only a slight decrease in cell viability occurred. All cell lines showed a similar tendency: the extent of electrical injury (EI) increased with the increase in pulse number and duration. However, there existed differences in heat sensitivity among organs.ConclusionsThis database can be used for the application of electroporation-based treatment (EBT) in the digestive system to predict cell survival and tissue injury distribution during the treatment.